Functional Materials Under Stress: In Situ TEM Observations of Structural Evolution. Issue 27 (20th November 2019) - Deng, Yu; Zhang, Ruopeng; Pekin, Thomas C.; Gammer, Christoph; Ciston, Jim; Ercius, Peter; Ophus, Colin; Bustillo, Karen; Song, Chengyu; Zhao, Shiteng; Guo, Hua; Zhao, Yunlei; et al.
Abstract: The operating conditions of functional materials usually involve varying stress fields, resulting in structural changes, whether intentional or undesirable. Complex multiscale microstructures including defects, domains, and new phases, can be induced by mechanical loading in functional materials, providing fundamental insight into the deformation process of the involved materials. On the other hand, these microstructures, if induced in a controllable fashion, can be used to tune the functional properties or to enhance certain performance. In situ nanomechanical tests conducted in scanning/transmission electron microscopes (STEM/TEM) provide a critical tool for understanding the microstructural evolution in functional materials. Here, select results on a variety of functional material systems in the field are presented, with a brief introduction into some newly developed multichannel experimental capabilities to demonstrate the impact of these techniques. Abstract : Several examples of current progress regarding in situ mechanical scanning/transmission electron microscopy techniques are addressed. Probing of local microstructures from atomic to micrometer scales in functional materials that are under high stress loads is possible. Advancements of these state‐of‐the‐art techniques make it possible to study the behavior of materials with unprecedented temporal and spatial resolution.